Bleeding jejunal metastases arising from primary alveolar soft part sarcoma of thigh (Indian Journal of Case Reports, 2018)
Alveolar soft part sarcoma (ASPS) is a rare tumor (0.5–1% of sarcomas) of unknown etiology with a highly characteristic morphology. It tends to occur more often in the younger age group with a predilection for the female sex. Prognosis is generally poor and it often presents with late metastases. Here, we report the case of a 48-year-old female, who presented to the emergency department with a complaint of giddiness and melena. She was a known case of sarcoma ASPS left thigh with pulmonary secondaries. On evaluation, a bleeding tumor in the upper jejunum was found on upper GI endoscopy. As the patient’s hemodynamics were unstable, she had to be operated without further imaging. Post-operative period was uneventful.